Incontinentia pigmenti: MR demonstration of brain changes. - Pascual-Castroviejo, I; Roche, M C; Martinez Fernández, V; Perez-Romero, M; Escudero, R M; Garcia-Peñas, J J; Sanchez, M (American Journal of Neuroradiology, 1994)
PURPOSE To describe the MR findings in eight girls and women with incontinentia pigmenti, from two families. Four had skin lesions and neurologic disease, and four had only skin lesions. METHODS Eight patients had physical examination, family history, electroencephalogram and MR examination of the brain. MR was repeated in the two cases with more severe changes several years after the first study. RESULTS MR revealed brain changes only in the four patients who had neurologic disease associated with the cutaneous lesions of incontinentia pigmenti. Abnormalities were located in the cerebral hemisphere contralateral to the most affected side of the body. In two cases, the MR changes were subjacent to the scalp areas where the most severe cutaneous lesions were located in the neonatal period. Hypoplasia of the corpus callosum, probably secondary to atrophy of one or both cerebral hemispheres, and abnormal signal and atrophy of the lateral regions of one of the cerebellar hemispheres also were found in all four cases. Although the changes were seen in both the T1- and T2-weighted images, they were most evident in the latter. The four patients in the fourth stage who had only cutaneous lesions without neurologic problems did not reveal any MR abnormalities. CONCLUSIONS This study demonstrates MR signal changes and focal atrophy of the cerebrum, cerebellum, and corpus callosum in patients with incontinentia pigmenti and neurologic disorders. The MR images appear normal in patients with incontinentia pigmenti who have no neurologic abnormalities.